Enhanced recovery after surgery: A new approach to optimize surgical outcomes and reduce costs - Williams, Carla; Laflamme, Claude (Operating Room Nurses Association of Canada Journal, 2024)
Enhanced Recovery After Surgery is an evidence-based approach to surgical care aimed at minimizing the stress of surgery and supporting patients to recover quickly. Its perioperative care pathways aim to promote patient mobilization, reduce complications after surgery, support shorter hospital stays, minimize hospital readmissions, and reduce costs. The program follows patients through all stages of the process, from pre-op to post-op, and has been shown to improve safety outcomes. In 2017, Enhanced Recovery Canada was formed to support the implementation of surgical best practices for all Canadians. Surgical pathway tools and patient resources are now available to support the most frequent surgeries that touch every operating room across the country, including colorectal surgeries, gynecologic surgeries, and inpatient/outpatient orthopaedic hip and knee replacements.